Perancangan Sistem Informasi Akuntansi Pada IQ Salon - Santoso, Kartika Imam; Sundari, Cisilia; Kusumasari, Putri (Universitas Diponegoro, 2014)
Recording of transactions and financial statements of the manual on IQ Salon raises the risk of error in the financial records are not fast and precise, and cause difficulties with the increasing transaction will occur in the future. The purpose of this research is to design accounting information systems (AIS) to prepare financial statements to the income statement and provide convenience in recording daily transactions and the financial statements in order to avoid mistakes. The design used in this study is a Waterfall and programming used is PHP and MySQL as the database. The design uses modeling context diagram, Data Flow Diagrams (DFD), Entity Relationship Diagram (ERD). Accounting information system on IQ Salon built using the programming language PHP and MySQL as the database generates Journal report, Balance Sheet and Income Ledger. The report simplify IQ Salon owners to control and make decisions. It is also easier for employees to serve customers in the event of payment of the services that have been awarded Keywords : DFD; IQ Salon; MySQL; PHP; IAS; Waterfall